147 PERITONEAL PAPILLARY SEROUS CARCINOMA IN WOMEN: A 10-YEAR STUDY AT A COMMUNITY HOSPITAL. (1st January 2005) - Malani, A.; Mankan, N.; Sridhar, S.; Hussain, S.
Abstract : Objective: Mullerian papillary serous tumors are a spectrum of gynecological tumors. We reviewed papillary serous carcinoma of peritoneum (PSCP) and compared its clinical behavior to stage III and IV of ovarian, uterine, and fallopian tube papillary serous carcinomas. Methods of Study: Medical records and pathological records were reviewed for the period from November 1992 to July 2002, at Coney Island Hospital, Brooklyn, NY. There were 6 patients with PSCP and they were compared with 8 patients with ovarian papillary serous carcinoma (OPSC), 5 patients with uterine papillary serous carcinoma (UPSC), 2 with fallopian tube papillary serous carcinoma (FTPSC), and 1 with multifocal papillary serous carcinoma. Symptoms of abdomen distention and pain, loss of appetite, weight loss, vaginal bleed, and signs of ascites, palpable mass, uterine polypoid mass and laboratory data of CA-125 at admission were compared. The pathological grade, postoperative residual disease, recurrence, disease-free survival (DFS) and overall survival (OS) were also compared. Results: Patients with UPSC were older than PSCP and OPSC. The commonest symptoms in patients with PSCP and OPSC were abdominal pain, distention, and ascites compared to women with UPSC who presented with vaginal bleeding and polyp or polypoidal mass in uterus. Mean CA-125 levels were lower in patients with PSCP (539.00 U/mL) compared to OPSC (2996.70 U/mL). Overall patients with OPSC and UPSC had a better DFS and overall survival compared to those with PSCP. Also, low-grade tumors in all groups had a better survival and DFS compared to those with moderate and high grade tumors within the same group. Conclusions: The patients with PSCP had poorer OS and shorter DFS compared to OPSC and UPSC. Patients with high-grade tumor had residual disease after debulking surgery. Overall low-grade tumors in all groups had a better OS and DFS compared to moderate and high-grade tumors within the same group. Also, patients with high-grade OPSC and PSCP and higher levels of CA-125 at the time of diagnosis had a poorer outcome.